Special damage: discussion on its autonomy as one of the foundations of objective responsibility - Lizcano Orozco, Rosana (DIXI, 2013)
This article shows a careful jurisprudential analysis of the statements of the State Council, as the highest court of administrative litigation, dealing with the notion, extent, and scope of the application of special damages as the security allocation of state responsibility. The paper expresses how special damages, beyond integrating a security allocation for the strict liability system, are the very base of the system since the elements that integrate them are present in other security allocations for strict liability, which challenges its independence.
Keywords: State Council; special damages; State responsibility; objective system of liability